The temporality of Perdigões enclosures: absolute chronology of the structures and social practices - Valera, António Carlos; Silva, Ana Maria; Márquez Romero, José Enrique (SPAL - Revista de Prehistoria y Arqueología, 2014)
Thirty five radiocarbon dates for the Neolithic and Chalcolithic ditched enclosure of Perdigões (Reguengos de Monsaraz, Portugal) are presented. After a discussion of some of the problems of dating negative structures, a chronological sequence is presented for the ditch structures and for the social practices related to funerary behaviours and the manipulation of human remains. A clear Neolithic phase is identified, well separated chronologically from the Chalcolithic one. The possibility of the gradual and eventually interrupted development of the site, is discussed. Funerary contexts and the manipulation of human remains are present from the earliest phase of the site, but the practices became significantly diverse during the 3rd millennium by the end of which the site seems to decay and significant activity seems to stop.